Evaluation of the results of flexible ureterorenoscopy by retrograde nephrolithotripsy by laser at Le Van Viet Hospital from 2022 to 2025 - Ly, Nguyen Khoa; Uyen, Nguyen Thi Bich; Lam, Pham Son (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Introduction: The study evaluated the results and factors related to the treatment of kidney stone patients undergoing retrograde nephrolithotripsy by flexible ureterorenoscopy with Holmium laser at Le Van Viet Hospital from August 2022 to July 2025. Methods: A retrospective, cross-sectional, descriptive study. Results and discussion: The study included 34 patients: 21 males (61.8%) and 13 females (38.2%). The average age of patients was 53.8 ± 13.2 years. The common reason for hospitalization was low back pain, which accounted for 55.8%. 4.7% of patients had hypertension, 23.6% had diabetes, and 11.8% had both conditions. 15 patients (44.12%) underwent surgery for urinary stones with a total of 21 times, the proportion of ureteroscopy (URS) and percutaneous nephrolithotomy (PCNL) was 57.15% and 23.81% respectively. Mean size stone: 15.76 ± 6.56 mm (6 - 35 mm). Stent DJ (JJ) used in all patients for at least 2 weeks, and they had urine cultures free of infection before flexible ureterorenoscopy. The average surgery time was 74.71 ± 26.88 minutes, the success rate was 97.1% and the average hospital stay was 6.56 ± 1.62 days. Conclusion: Treating kidney stones undergoing retrograde nephrolithotripsy by flexible ureterorenoscopy with Holmium laser is a safe and effective method with a high stone clearance rate. In our study, with a procedure involving the placement of a stent at least 2 weeks before surgery, the results showed 47.1% stone-free after 1 month, 79.5% after 3 months, and 97.1% after 6 months.